Development of Android-Based Interactive Learning Media on Listening, Imitating, and Reciting Materials for PAUD Students - Ari, Novi Hendri; Veza, Okta; Simatupang, Wakhinuddin; Irfan, Dedy; Muskhir, Mukhlidi; Riyanda, Afif Rahman; Daphiza, Della (Jurnal Pendidikan MIPA, 2021)
At the Al-Qur'an-based PAUDQ An Najah, they are required to innovate in learning activities during the pandemic. The learning media used in PAUDQ An Najah still uses paper media, so teachers have difficulty providing material during the pandemic. Researchers feel the need to develop android-based interactive learning media to improve the quality of learning during the Covid19 pandemic. The purpose of this study is to develop interactive learning media for the introduction of android-based Arabic vocabulary to assist teachers in the teaching process and to assist the role of parents in providing learning guidance to their children. The method used is Multimedia Development Life Cycle (MDLC), which has concept, design, material collecting, assembly, testing and distribution stages. This research produces interactive learning media applications that can be operated on parents' smartphones to support online learning. The conclusion of this study is that android-based interactive learning media is feasible to be applied to PAUDQ An Najah.Keywords: Interactive Learning Media, MDLC, Android, PAUD DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp279-291